Avaliação do potencial anti-inflamatório e antioxidante da casca da jabuticaba (Myrciaria cauliflora), do açaí jussara (Euterpe edulis Martius) e do jambolão (Syzygium cumini) em camundongos submetidos à dieta de cafeteria - Sant'Ana, Marcella Ramos (2014)
Increased body fat is associated with increased inflammation and oxidative stress, which may compromise the health of the individual. An alternative to try to restore the oxidative and inflammatory balance of the body would be the intake of antioxidant compounds such as polyphenols present in fruits such as jaboticaba (Myrciaria cauliflora), the jambolan (Syzygium cumini) and jussara açai (Euterpe edulis Martius), fruit with low consumption, but with a large production in southeastern Brazil. The objective of this study was to investigate the effect of supplementation of these fruits on oxidative stress and inflammation in animals fed a high calorie and high fat diet. The fruits were lyophilized and subsequently evaluated its chemical composition and concentration of total phenolics, anthocyanin and antioxidant activity. For the biological assay, 30 adult male mice of the Swiss race divided into 5 groups (n = 6/group) were used, namely: group treated with standard commercial diet (negative control), group treated with cafeteria diet (positive control) and test groups that received the cafeteria diet plus 2% freeze-dried jaboticaba peel powder or jambolan or acai jussara for 14 weeks. After the experimental period was evaluated serum antioxidant capacity and lipid peroxidation as well as the levels of the anti-inflammatory (IL-10) and proinflammatory cytokines (TNF-a and IL-6). It was applied t test to compare the results of the control groups and ANOVA, complemented with Tukey test (a = 5%), to compare the results between the tests groups and the positive control. The freeze-dried acai jussara powder was the fruit with higher concentrations of anthocyanins, while the jaboticaba peel showed the highest concentrations of phenolic compounds and antioxidant activity in vitro. Supplementing with freeze-dried fruits was effective in increasing serum antioxidant activity in experimental animals, but no reduction of serum lipid peroxidation was observed. Regarding the inflammatory profile, no difference between the animals supplemented with freeze-dried fruits and receiving only cafeteria diet was observed. It can be concluded that the fruits tested were effective in increasing serum antioxidant activity of the supplemented animals, but showed no anti-inflammatory effect in these animals.